THE INFLUENCE OF PHOSPHATE COPRECIPITATION ON RARE EARTH DISTRIBUTIONS IN NATURAL WATERS - Byrne R.H.; Xuewu L.; Schijf J. (My University, 1996)
Although the rare earth elements (REEs) are thought to participate in essentially all of the processes that influence metal distributions in seawater, quantitative descriptions of oceanic rare earth element (REE) distributions have nearly exclusively involved removal of these elements from solution via adsorption on settling particles. Laboratory investigations involving yttrium (Y) and all REEs, except Pm, demonstrate that phosphate coprecipitation of Y and the REEs creates solution concentration patterns characteristic of input-normalized Y and REE concentrations in seawater. Removal of the REEs, and Y, from solution as phosphate coprecipitates depletes REEs in solution relative to Y, depletes solutions in Sm relative to heavier and lighter elements (relative depletions of the middle REEs), and produces a variety of near-neighbor concentration anomalies (e.g., Eu-Gd-Tb, Dy-Er-Yb, and Er-Yb-Lu) which have been reported in high precision analyses of open ocean waters.